2021
DOI: 10.1097/md.0000000000027069
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the microcirculation of retinochoroid capillary between acute and chronic central serous chorioretinopathy with OCTA

Abstract: To investigate the difference in chorioretinal microcirculation between acute central serous chorioretinopathy (aCSC) and chronic central serous chorioretinopathy (cCSC) using optical coherence tomography angiography. In total, 65 patients previously diagnosed with central serous chorioretinopathy (33 aCSC and 32 cCSC) were included in our cross-sectional study. All patients underwent complete ophthalmologic assessment including logarithm of the minimum angle of resolution best-corrected visual acui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In agreement with that, Cakir et al [25] , Wang et al [26] , Han et al [27] and Lu et al [28] concluded that the vessel density of superficial CC was significantly lower in eyes with acute CSC than in fellow eyes and in age and refractive error matched normal eyes.…”
Section: Ahlers Et Al [22] and Yang Et Al [21]supporting
confidence: 85%
“…In agreement with that, Cakir et al [25] , Wang et al [26] , Han et al [27] and Lu et al [28] concluded that the vessel density of superficial CC was significantly lower in eyes with acute CSC than in fellow eyes and in age and refractive error matched normal eyes.…”
Section: Ahlers Et Al [22] and Yang Et Al [21]supporting
confidence: 85%
“…40 Changes in the microcirculation of the retina may be an early stage of some diseases but relevant mechanism has not been studied in sufficient detail. [41][42][43] It is not yet clear whether there is a correlation between perfusion pressure, CDE and vessel density, between changes in blood flow and changes in retinal thickness or macular oedema. Our study will devote to analysing the clinical significance of changes in vessel density after cataract surgery and whether there is a difference in the effect of surgery on blood flow under the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the advent of OCTA, which helps to visualise and analyse the retinal vasculature in a non-invasive way and allows quantitative calculation of vessel density with the aid of specific software 40. Changes in the microcirculation of the retina may be an early stage of some diseases but relevant mechanism has not been studied in sufficient detail 41–43. It is not yet clear whether there is a correlation between perfusion pressure, CDE and vessel density, between changes in blood flow and changes in retinal thickness or macular oedema.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous studies, we found higher density of choriocapillaris in cCSC than in aCSC at the inferotemporal subfield. We hypothesized that the hypoperfusion with surrounding hyperperfusion on OCTA may be the compensatory status due to ischemia in cCSC [31][32][33] . However, in contrary to some published studies 34,35 , we found the choroidal thickness and volume, as well as large-vessel density were higher in the aCSC group.…”
Section: Discussionmentioning
confidence: 99%